Ethics in youth sport policy and pedagogical applications - Harvey, Stephen 1973-; Light, Richard 1951- (Routledge studies in physical education and youth sport, 2013)
In this study of ethical issues in and around youth sport, leading international experts argue for the development of strong ethical codes for the conduct of youth sport and for effective policy and pedagogical applications to ensure that the positive benefits of sport are optimized and the negative aspects diminished